(3GdCQHYhfs - (3GdLHYj, GdYGedj, GdMGQKj, YR GdOjf, MSjf Hf YHO GdUeO Hf eMeO Hf Ydj, J (B984(3g`s ((3eMeO Hf ESeGYjds)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeI GdbQGQ(B...(3ajbhd(B... (3MSjf Hf YHO GdUeO(B... (3deG gLQJ aj gPG GdReGf CMGOjK Ggd GdHjJ(B...s
(3BNQgG (B:s
(3hbGd Ydjg GdSdGe(B: (3EPG CJJ Ydi GdQLd CQHYhf SfI bjd dg(B: (3NP MPQc(B... (3aGYed deG CeGec ef Gdghd hOY Yfc aVhd Gdbhd(B. (3JeJ GdCMGOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B615s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs